Effects of a 12-day maximal shuttle-run shock microcycle in hypoxia on soccer specific performance and oxidative stress - Gatterer, H.; Klarod, K.; Heinrich, D.; Schlemmer, P.; Dilitz, S.; Burtscher, M. (Applied Physiology, Nutrition, and Metabolism, 2015)
The purpose of this study was to investigate the effect of a maximal shuttle-run shock microcycle in hypoxia on repeated sprint ability (RSA, 6 × 40-m (6 × 20 m back and forth, 20" rest in between)), Yo-Yo-intermittent-recovery (YYIR) test performance, and redox-status. Fourteen soccer players (age: 23.9 ± 2.1 years), randomly assigned to hypoxia (~3300 m) or normoxia training, performed 8 maximal shuttle-run training sessions within 12 days. YYIR test performance and RSA fatigue-slope improved independently of the hypoxia stimulus (p < 0.05). Training reduced the oxidative stress level (-7.9%, p < 0.05), and the reduction was associated with performance improvements (r = 0.761, dRSA; r = -0.575, dYYIR, p < 0.05).